Between you & me : confessions of a Comma Queen - Norris, Mary, 1952- (W.W. Norton & Company, 2015)
A New Yorker copy veteran presents laugh-out-loud descriptions of some of the most common and vexing errors in language and usage, drawing on examples from classic literature and pop culture while sharing anecdotes from her work with celebrated writers.